Preceptorship of Student Nurses in Ghana: A Descriptive Phenomenology Study - Nancy Innocentia Ebu Enyan; Christian Makafui Boso; Sarah Ama Amoo (Nursing Research and Practice)
Background. Preceptorship plays an integral part in the clinical training of nursing and midwifery students, especially in high-income countries where it is a well-accepted concept. However, in Ghana, most nurses and midwives do not view preceptorship as part of their role. Aim. The aim of this study was to explore the lived experiences of preceptorship of student nurses and the challenges confronting the preceptorship role. Methods. A descriptive phenomenological study was conducted with 22 purposively selected preceptors aged 34 to 56 years from five clinical placement sites in the Cape Coast Metropolis in the Central Region of Ghana. Most of the participants had been preceptors for two to 18 years. In-depth interviews were conducted with the aid of a semistructured interview guide and analysed by qualitative thematic analysis inspired by Braun and Clarke’s description of the method. Results. The essence of the phenomenon has been captured in three main themes: (1) being excited about the role as it offered opportunities to learn and build relationship with students. (2) Encountering challenges including student’s unwillingness to learn, absenteeism, and disrespect and also lack of interest of staff to assist students, time constraints, workload, burnout, parallel schedules of preceptors, and large student numbers, and (3) the need for effective collaboration between educational institutions and hospitals. Conclusions. Though preceptors were excited about precepting student nurses, the challenges associated with it are multidimensional which requires effective collaboration between educational institutions and clinical placement sites.